Physical Health Outcomes of Bereaved Parents - Murphy, Savannah (East Carolina University, 2021)
Purpose: The purpose of this study is to identify bereaved parents’ long-term physical health outcomes, including sleep, and changes in health risk behaviors, such as smoking and drinking alcohol. Background and Significance: A child’s death is one of the most traumatic events an individual can experience. Individuals who experience it are more likely to have adverse health outcomes including increased morbidity and mortality. There is little evidence of long-term health outcomes of bereaved parents in the United States. It is important to study bereaved parents’ health outcomes to plan parental bereavement care. Methods and Analysis: This study used a cross-sectional, survey design to assess bereaved parent’s health whose child (0- <19 years) had died within the past 10 years. A convenience sampling technique was used to enroll participants using the decedent database from a tertiary care hospital. Questionnaires were sent to eligible parents using a secured database (REDCAp). Questionnaires included a demographic data survey and a survey to assess sleep disturbance (PROMIS_Sleep). The demographic survey included assessment of history of past illness (e.g. diabetes or hypertension) and change in smoking and alcohol intake. Participants indicated their overall health perception on a visual scale of 0 to 100. Health risk indicators were summarized using descriptive statistics. Findings: The data analysis identified sleep disturbances (83%) with 6% reporting more than 1 SD worse than normative data. Sleep disturbance was associated with increased alcohol use since the child’s death (F=8.0; p=0.006). Participants (20%) reported initiating or increasing tobacco or alcohol use after their child’s death.
Keywords: bereavement; nursing; health outcomes